Key physical wood properties in termite foraging decisions. Issue 149 (12th December 2018) - Oberst, Sebastian; Lai, Joseph C. S.; Evans, Theodore A.
Abstract : As eusocial and wood-dwelling insects, termites have been shown to use vibrations to assess their food, to eavesdrop on competitors and predators and to warn nest-mates. Bioassay choice experiments used to determine food preferences in animals often consider single factors only but foraging decisions can be influenced by multiple factors such as the quantity and quality of the food and the wood as a medium for communication. A statistical analysis framework is developed here to design a single bioassay experiment to study multifactorial foraging choice ( Pinus radiata ) in the basal Australian termite species Coptotermes ( C. ) acinaciformis (Isoptera: Rhinotermitidae). By employing a correlation analysis, 17 measured physical properties of 1417 Pinus radiata veneer discs were reduced to five key material properties: density, moisture absorption, early wood content, first resonance frequency and damping. By applying a fuzzy c -means clustering technique, these veneer discs were optimally paired for treatment and control trials to study food preference by termites based on these five key material properties. A multifactorial analysis of variance was compared to a permutation analysis of the results indicating for the first time that C. acinaciformis takes into account multiple factors when making foraging decisions. C. acinaciformis prefer denser wood with large early wood content, preferably humid and highly damped. Results presented here have practical implications for food choice experiments and for studies concerned with communication in termites as well as their ecology and coevolution with trees as their major food source.